O ensino de história e cultura afro-brasileira e africana no contexto escolar: percepções de professores/as acerca da implementação da lei nº 10.639 de 2003 - Serrano, Daiane Duprat (2019)
Law nº 10.639 de 2003 establishes the compulsory teaching of African and Afro-Brazilian history and culture in the curricula of basic education in all Brazilian territory. The present investigation discusses the implementation of the mentioned law in the State School Professor Abel Freire Coelho, in the city of Mossoró, state of Rio Grande do Norte, and the subjects of the research are five teachers of the institution's high school. For the development of the study, it was used as a methodology the school ethnography – an adaptation of the ethnographic method for educational research – whose stages are visits to the school, on-site observations, informal conversations, questionnaires and semi-structured interviews with five teachers of the disciplines of the subjects Arts, Portuguese, Spanish, History and Sociology, to identify the presence of the theme based on their perceptions. Also, in order to achieve the objectives established in the study, the national curriculum guidelines for the education of ethnic-racial relations and for the teaching of Afro-Brazilian and African history and culture and the pedagogical political project of the school were analyzed. As a theoretical framework, we soughtsupport in Fernandes (1978), Gomes (2005), Munanga (2012), Munanga; Gomes (2016), Nascimento (1982), Ribeiro (2014), to study the issue of racism in Brazil, Black Movement, culture, identity and difference; Silva (2017), Lopes (2008) and Macedo (2012) to discuss curriculum and curriculum guidelines, as well as André (2000) and DaMatta (1978) to support ethnographic research. Considering what was observed in the school, as well as the analysis of the interviews with the teachers, we verified the school partially implements the precepts established in Law nº 10.639 de 2003, since the political pedagogical project does not include expressly the theme prescribed in the legislation